STRATEGI KPUD LAMONGAN DALAM MENINGKATKAN PARTISIPASI PEMILIH PENYANDANG DISABILITAS DI KABUPATEN LAMONGAN PADA PEMILU SERENTAK 2019 - Zuli Kasmawanto; Santi Nurjannah (LPPM UNISDA, 2021)
Elections in Indonesia cannot be separated from voters with disabilities. Not all humans are created perfectly. Some of our brothers and sisters have to live with various deficiencies, one of which is a person with a disability (diffable / different ability). In reality, people with disabilities remain the most vulnerable group in society. One of the difficulties faced in the political field is the implementation of general elections in using their voting rights. The Lamongan KPUD needs to implement the right strategy in an effort to increase the participation of voters with disabilities. This research uses descriptive qualitative research methods. Qualitative research itself is research that as a whole makes use of interpretive methods by presenting in the form of descriptions. The results of the research obtained are that the Lamongan KPU as the election organizer has implemented a strategy to increase the participation of voters with disabilities by providing socialization and simulations regarding general elections, involving persons with disabilities by conducting a Democratic Volunteer Recrumem, some of whom are persons with disabilities.